Paulo Freire's research itinerary: contributions for promoting health in the teaching profession - Fabiano Oliveira Antonini; Ivonete Teresinha Schülter Buss Heideman
ABSTRACT Objectives: examine Paulo Freire's research itinerary as a theoretical-methodological framework and its contributions for promoting health in the teaching profession. Methods: qualitative participatory action research coordinated with Paulo Freire's itinerary, carried out in culture circles, from April 18, 2018 to June 26, 2018. It involved the participation of 21 teachers from a federal teaching institution. Results: the method that was used promoted dialogue and reflection among the participants, enabling a health promotion intervention. It facilitated self-knowledge and reflection, resulting in significant changes in the participants, in a process in pursuit that seeks transformations. Final Considerations: Paulo Freire's research itinerary was opportune, as a possibility for promoting health, mainly in terms of providing a framework that assists in the practical construction of knowledge and encourages participants to examine their reality in the pursuit of enhanced quality of life.